Models for assessing the impact of land use change on food security and sustainability: a review (Revista Sistemas de Producción Agroecológicos, 2026)
This article sought to identify the main models for assessing the impact of land use change on food security and sustainability at the global level. The trends obtained from the literature review allowed us to recognise the geographical distribution, the typology of the most widely used models, the application approach and the associated variables. This review was based on a systematic search of related articles in four scientific databases over a 10-year period (2013-2023). The results show that the most widely used model worldwide is the CA-Marcov model, with Asia and Africa being the continents where it is most commonly applied, especially in approaches associated with agriculture and climate change. It was also found that variables associated with crops (Q4), urban cover (Q3), vegetation (Q3) and water bodies (Q3) are preferred for the construction of models to assess the impact of Land-Use-Land-Cover (LULC) change on food security and sustainability. These variables are related to biophysical factors (Q2), demographic pressure (Q2) and roads or pathways (Q1). It is suggested that the models detected involve multidimensional variables that allow for the representation and prediction of phenomena associated with LULC changes that have an impact on scenarios that are far from food security and sustainability. It is suggested that the models detected involve multidimensional variables that allow for the representation and prediction of phenomena associated with LULC changes that have an impact on scenarios that are far from food security and sustainability.